Bioactive lipid-nanoparticles with inherent self-therapeutic and anti-angiogenic properties for cancer therapy. (February 2023) - Cao, Shuwen; Zhang, Wenyue; Pan, Hehai; Huang, Ziqi; Guo, Mingyan; Zhang, Lei; Xu, Xiaoding; Saw, Phei Er
Abstract: Angiogenesis inhibition has become a promising therapeutical strategy for cancer treatment. Current clinical anti-angiogenesis treatment includes antibodies against vascular endothelial growth factor (VEGF) or VEGF receptor, fusion proteins with high affinity to VEGF receptor, and tyrosine kinase inhibitors of VEGF receptor. However, current treatments are prone to systemic toxicity or acquiring drug resistance. A natural bioactive lipid 1, 2-dipalmitoyl-sn‑glycero-3-phosphate (dipalmitoyl phosphatidic acid, DPPA) was reported to exhibit anti-angiogenic and anti-tumoral activity. However, the hydrophobic property of DPPA largely restricted its clinical use, while systemic infusion of free DPPA could result in undesirable side effects. Herein, we successfully developed DPPA-based lipid-nanoparticles (DPPA-LNPs) which turns the "therapeutic payload into nanocarrier". This strategy could improve on DPPA's hydrophiliciy, thereby facilitating its systemic administration. . DPPA-LNPs not only retained the therapeutic anti-angiogenic and anti-tumoral bioactivity of parental DPPA, but also greatly improved its tumor targeting ability via enhanced permeability and retention (EPR) effect. This strategy not only eliminates the limitation of drug encapsulation rate, toxicity of the delivery vehicle; but also enhances DPPA bioacvtity in vitro and in vivo . Systemic administration of DPPA-LNPs significantly suppressed the blood vessel formation and tumor growth of triple negative breast cancer and liver cancer growth on both xenograft tumor models. Statement of significance: This is the first-in-kind self-therapeutic inherent lipid to be made into a nanocarrier, with inherent anti-angiogenic and anti-tumor properties. DPPA nanocarrier is fully natural, fully compatible with minimal systemic toxicity. DPPA nanocarrier can accumulate at high concentration at tumor via EPR effect, exerting both anti-angiogenic and anti-tumor effects in vivo . DPPA nanocarrier could be used to encapsulate biologics or small molecules for synergistic anti-cancer therapy. Graphical abstract: Image, graphical abstract